Utilization of Welding Electrode Waste To Purify Biogas From Hydrogen Sulfide Impurities - Kristiawan, Timotius Anggit; Apriandi, Nanang; herlambang, Yusuf Dewantoro; Setiyawan, Trio; Wibowo, Andryana Dwiandara (Eksergi, 2023)
Abstract”” The biogas desulphurization process has a crucial role in the widespread use of biogas due to the toxic and corrosive nature of the element hydrogen sulfide on equipment. This study investigated the potential use of waste welding electrodes as a biogas purification medium. Variables in the form of feed biogas flow rates of 1, 2, and 3 liters/minute were studied for their effects. As a result, the most optimum performance was obtained in the test with a feed biogas flow rate of 1 liter/minute, with an average reduction percentage of hydrogen sulfide content in the biogas of 27.12%.